Institutional reforms in public sector what did we learn? - Baimyrzaeva, Mahabat (Research in public policy analysis and management ;, 2012)
What does it take to design effective government institutions and sustain positive changes? What have we learnt about the attempts to deliberately design and redesign public sector institutions in different countries? What works and what doesn't, and why? What happens when reforms fail? This book looks at what the existing academic literature tells us about these questions, and intends to answer these questions to generate and define theoretical and practical knowledge about deliberate (vs. evolutionary) public sector institutional change. It analyzes lessons from changes implemented by international development agencies working to reform public sector institutions in developing countries over the last five decades. The book details reforms in one such country; Kyrgyzstan, one of the more diligent nations in undertaking donor-guided reforms since its independence in 1991. It then presents a conceptual framework and analytical tools essential for understanding the processes used in deliberate institutional change, and in planning for and implementing institutional reform.